Menelaah Hubungan Potensi Credit Crunch Modal dan Aset Perbankan - Holik, Abdul (PPPM POLTESA, 2024)
Banking system has to face uncertainty when outbreak of COVID-19 started from Wuhan, Cina. This research tries to find the relationship among potency of credit crunch, capital, and asset. We focus on the credit crunch phenomenon which can hamper the banks’ capability. This research conducted with period since January 2019 until December 2020. Based on the analysis of VAR and VECM, by including variable ATMR/ Kredit (as a proxy for credit crunch potential), asset, and capital that banks hold, we find the differences among the group of Bank BUKU 1, Bank BUKU 2, Bank BUKU 3, dan Bank BUKU 4, in responding potency of credit crunch. From the result it is found among Banks BUKU 1 that potency of credit crunch has negative impact on capital, but not have significant impact on asset. Interestingly among Banks BUKU 2 we find that impact of potency of credit crunch does not appear on capital, but has significant impact on asset. In the group of Bank BUKU 3, potency of credit crunch has not impact on both capital and asset. In the group of Bank BUKU 4, we find that potency of credit crunch influences capital negatively only at lag-1, while at lag-2 and lag-3 the impact is positive. It has impact on asset positively since lag-1 until lag-3. The outbreak of COVID-19 was responded quickly by stakeholders in Indonesia by empowering business through digitalization and new policies that overcome many obstacles.